Responsible driving (Glencoe/McGraw-Hill, 2000)
This classroom-tested program, developed with the American Automobile Association (AAA), reflects the changes surrounding teen driving. Everything your students need to know about driving is included - from graduated driver licensing to zero tolerance laws to information about vehicle maintenance.